Pengaruh Job Stress dan Work Family Conflict Terhadap Job Satisfaction Yang Dimediasi Oleh Job Burnout Pada Karyawan Perusahaan Pakan Ternak di Grobogan - Aseanty, Deasy; Wahyu Gunawan, Andreas; Deddy Maha Dikka, Muhamad (GEMA EKONOMI, 2023)
This study aims to analyze the effect of Job Stress and Work Family Conflict on Job Satisfaction mediated by Job Burnout in employees of animal feed companies in Grobogan, Central Java. The data used in this study is primary data. The research method used in this study is quantitative descriptive. The sample method used was purposive sampling with 105 employees. Hypothesis testing using SEM analysis. It was found that there was no positive effect of Job Stress on Job Burnout. It was later found that there was a positive influence of Work Family Conflict on Job Burnout. The results of testing hypothesis 3, it was found that there is a negative effect of Job Burnout on Job Satisfaction. Employees' boredom and boredom of work triggers an increase in Job Burnout which leads to a decrease in their Job Satisfaction level. It was found that there was no negative effect of Job Stress on Job Satisfaction mediated by Job Burnout. This indicates that employee job burnout cannot mediate the relationship between job stress and job satisfaction. There is a negative effect of Work Family Conflict on Job Satisfaction mediated by Job Burnout. This indicates that Job Burnout experienced by employees plays an important role in mediating the relationship of Job Stress to Job Satisfaction